Development of Maritime Economy and Coastal Economy to Improve Competitiveness and Coastal Economic Growth in Riau Island Province - Tumpal Manik; Iranita Iranita; Henry Eryanto; Karuniana Dianta A. Sebayang (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2019)
This research aims to analyze and examine the influence of maritime economic development and the economy of coastal communities in improving maritime competitiveness and coastal economic growth. Maritime economics is analyzed based on the fisheries sector, marine tourism and shipping. The economics of coastal communities are analyzed based on community empowerment, development and welfare. This research was conducted in Riau Islands Province. This reseach uses a qualitative method with a questionnaire of 330 respondents. The processing of research data by validity test, reliability, t-test, F-test and Adjusted R Square. The result of H1 that maritime economic development affect on competitiveness of maritime regions. Its are the fisheries sector 8.3%, the tourism sector 2.51%. H2 the economic development of coastal communities affects on competitiveness of maritime regions that are empowerment 23.2%, to increase welfare 31.8%. The development no significant effect. H3 the maritime economic development affects coastal economic growth through the fisheries sector 18%, the tourism sector 18% and the shipping sector 12.5%. H4 hypothesis of economic development of coastal communities has significant effect on coastal economic growth, that are at community empowerment 12.5%, welfare 17.2%, development 6.8%.